Optimasi Konsentrasi dan Waktu Kontak Ekstrak Daun Jati (Tectona grandis) sebagai Alternatif Safranin pada Pewarnaan Gram - Syafitri, Andita Izmi; Sufa, Hafizah Ilmi; Kurniati, Iis; Merdekawati, Fusvita (Politeknik Kesehatan Kemenkes Bandung, 2024)
Safranin is a cationic dye and is one of the harmful substance, in addition to its relatively expensive price, safranin waste also has several harmful effects on health, so the various studies on the use of natural dyes as an alternative of safranin have been widely carried out. Teak leaves are one of the plants that have the potential to used as an alternative of safranin because they contain anthocyanin compounds. This study aims to determine the concentration and optimal contact time of teak leaf extract that can be used as an alternative of safranin. The research method used is a quasi-experiment by providing treatment with 25%, 50%, and 100% concentration variations also contact time variations of 0.5, 1, and 1.5 minutes. The results showed that teak leaf (Tectona grandis) extract could be used as an alternative of safranin in Gram staining of E. coli and S. aureus. The conclusion of this study is that the optimum concentration of teak leaf extract is 50%, and the optimum contact time of teak leaf extract in Gram staining is 0.5 minutes.